OVERVIEW OF FASTING BLOOD GLUCOSE LEVELS IN HYPERTENSION PUSHERS IN THE WORKING AREA OF PUSKESMAS, EAST CITY - Firda R. Thaib; Yusri Halada; Ni Luh Arwati (LPPM Universitas Bina Mandiri Gorontalo, 2021)
Based on data from the Gorontalo Province Health Office in 2018, the city of Gorontalo was ranked third in cases of hypertension. Hypertension is a major risk factor for DM. The relationship with DM is very complex, Hypertension can make cells insensitive to insulin (insulin resistant) while insulin plays a role in increasing glucose uptake in many cells and in this way also regulates carbohydrate metabolism, so that if there is insulin resistance by cells, the sugar levels in the blood can also experience interference. This study aims to determine the description of fasting blood glucose levels in hypertension patients using the high, low and normal POCT method in the working area of ​​the East City Health Center. This research is a quantitative descriptive study with a total of 33 samples. Using a glucometer. This research is processed through the IBM SPSS Statistic V25.0 program then the data is presented in tabular form and reported as a percentage using the Frequency Distribution formula. The results showed that the average high fasting blood glucose levels in hypertension sufferers were 15 (45.5%) whereas for hypertension patients who have low fasting blood glucose levels 0% for hypertension sufferers have normal fasting blood glucose levels 18 (54.5%), Suggestions are expected that people with hypertension maintain a regular diet, and for other researchers it is hoped that they can increase the number of samples and use other methods so that the results obtained are maximized.